Never say never again [videorecording (DVD)] - Connery, Sean; Brandauer, Klaus Maria; Sydow, Max von, 1929-2020; Carrera, Barbara; Basinger, Kim, 1953-; Casey, Bernie; McCowen, Alec; Fox, Edward, 1937-; Semple, Lorenzo, Jr., 1923-2014; Kershner, Irvin (NSNA Company : [MGM/UA Home Entertainment], 2000)
From the luxury yacht the length of a football field, Largo oversees a master plan of mayhem involving stolen cruise missiles, nuclear extortion, deadly video games and all the other evils in SPECTRE'S arsenal. James Bond, Agent 007, goes into battle with a fabulous flying motorcycle and other ghastly gadgets, including a fountain pen that can write you off with a bang.